Are Scores on Hofstede's Dimensions of National Culture Stable over Time? A Cohort Analysis. (August 2015) - Beugelsdijk, Sjoerd; Maseland, Robbert; van Hoorn, André
<x xml:space="preserve">Abstract</x> Hofstede's framework, which is based on survey data collected in the late 1960s and early 1970s, dominates quantitative culture research in international strategic management. However, as countries develop economically, modernization theory predicts shifts in cultural values, which likely affect countries' scores on Hofstede's work‐related values dimensions, in turn raising doubt about the continued relevance of this framework for global strategy researchers and practitioners. We examine how country scores on Hofstede's dimensions have developed over time by replicating Hofstede's dimensions for two birth cohorts using data from the World Values Survey. Results indicate that, on average, contemporary societies score higher on Individualism and Indulgence versus Restraint, and they score lower on Power Distance than do past societies. We find that cultural change is absolute rather than relative, meaning that countries' scores on the Hofstede dimensions relative to the scores of other countries have not changed very much. As a consequence, cultural differences between country pairs (i.e., cultural distances) are generally stable. We discuss the implications of our findings for global strategy research.